2018
DOI: 10.1001/jamaoncol.2017.4844
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Dietary Inflammatory Potential With Colorectal Cancer Risk in Men and Women

Abstract: Findings suggest that inflammation is a potential mechanism linking dietary patterns and colorectal cancer development. Interventions to reduce the adverse role of proinflammatory diets may be more effective among overweight/obese men and lean women or men and women who do not consume alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 38 publications
2
94
1
7
Order By: Relevance
“…For example, associations have been uncovered between CRC and moderate consumption of sugar-sweetened beverages,43 as well as high fructose corn syrup specifically in animal studies,44 both in the absence of obesity and metabolic syndrome. An inflammatory diet, characterised by high consumption of processed foods and high-glycaemic load carbohydrates, creates an environment conducive to colonic proliferation45 and appears to increase CRC risk 46. What remains uncertain is how these dietary elements might influence early-life gut health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, associations have been uncovered between CRC and moderate consumption of sugar-sweetened beverages,43 as well as high fructose corn syrup specifically in animal studies,44 both in the absence of obesity and metabolic syndrome. An inflammatory diet, characterised by high consumption of processed foods and high-glycaemic load carbohydrates, creates an environment conducive to colonic proliferation45 and appears to increase CRC risk 46. What remains uncertain is how these dietary elements might influence early-life gut health.…”
Section: Discussionmentioning
confidence: 99%
“…The EDIP includes 18 components that partially overlap with the AIDI (nine anti‐inflammatory and nine pro‐inflammatory) and was identified with a step‐wise linear regression analysis based on hsCRP, TNFα receptor 2 and IL‐6 . In a US‐based population, a significant association between the pro‐inflammatory diet potential (measured using the EDIP) and risk of colorectal but not ovarian cancer has been observed. Our results are also in line with the findings of a meta‐analysis of dietary patterns and all‐cause and CVD mortality , where a ‘prudent’ dietary pattern (high consumption of fruits, vegetables, wholegrains and fish), which partially overlaps with the AIDI components, was associated with lower risks of all‐cause (26% reduction, 95% CI: 14–32%) and CVD (19% (95% CI: 13–25%) mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Among at-risk individuals, erythrocyte membrane-bound omega-3 PUFA levels were inversely associated with anti-CCP/RF positivity [15]. Previous studies investigating EDIP found robust associations between EDIP scores and colorectal cancer risk but no association with ovarian cancer risk [16, 17]. Similar to previous studies investigating dietary/metabolic factors in RA, the inflammatory dietary pattern was important specifically in younger-onset seropositive RA, defined as ≤55 years [5, 6, 12].…”
Section: Discussionmentioning
confidence: 99%